Prostate radiotherapy in patients with metastatic hormone-sensitive prostate cancer: A systematic review and meta-analysis of randomised controlled trials - Navid Roessler; Marcin Miszczyk; Alessandro Dematteis; Fabio Zattoni; Tamás Fazekas; Filippo Carletti; Giuseppe Reitano; Akihiro Matsukawa; Ahmed R. Alfarhan; Angelo Cormio; Abdulrahman S. Alqahtani; Timo F.W. Soeterik; et al. (Clinical and Translational Radiation Oncology, 2025)
Introduction: The incidence of synchronous metastatic hormone-sensitive prostate cancer (mHSPC) is rising with the increasing use of next-generation imaging. Local radiotherapy (RT) was shown to improve survival in patients with mHSPC; however, new data require a re-assessment of the indication and value of local RT in mHSPC. Methods: In this prospectively registered systematic review and meta-analysis (CRD42025648251), we searched MEDLINE, Scopus, CENTRAL, and Google Scholar in March 2025 for phase 3 RCTs evaluating the addition of RT to systemic therapy to improve OS in mHSPC patients. Hazard ratios (HRs) were pooled using random-effects meta-analysis. Risk of Bias was assessed with Cochrane’s RoB 2 tool. Results: Out of the 10,615 individual records, we identified three RCTs: HORRAD (n = 432), STAMPEDE (n = 2,061), and PEACE-1 (n = 1,173). The systemic treatment included androgen deprivation therapy (ADT) in HORRAD, ADT ± Docetaxel in STAMPEDE, and ADT ± Docetaxel ± Abiraterone in PEACE-1 trial. Local RT was not associated with significantly improved OS in all patients (HR = 0.92; 95 % confidence interval [CI] 0.85–1.00; p = 0.06), or in those with low metastatic burden (HR = 0.74; 95 %CI 0.51–1.06; p = 0.1); however, exploratory analyses showed a significant improvement in androgen deprivation resistance-free survival (HR = 0.76; 95 %CI 0.70–0.82; p < 0.001). Local RT was associated with significant reduction in local prostate cancer related events in the HORRAD (18 % vs. 30 %) and PEACE-1 (12 % vs. 22 %) trials, but not in the STAMPEDE trial (49 % vs. 51 %). Conclusion: Local RT does not improve OS in unselected patients treated with modern systemic therapies for mHSPC. However, it delays ADT resistance and reduces local adverse events, with relatively tolerable toxicity. Future studies should refine selection criteria, ideally using PSMA-PET imaging, dynamic response markers, and/or genomic profiling, to identify mHSPC patients most likely to benefit from local RT.